Pengaruh Pengetahuan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Orang Pribadi Dimediasi Kesadaran Wajib Pajak - Mianti, Yosy Fryli; Budiwitjaksono, Gideon Setyo (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of knowledge and tax sanctions on individual taxpayer compliance mediated by taxpayer awareness. The method of determining the sample using incidental sampling. Individual taxpayers who are registered at the Pratama Surabaya Mulyorejo Tax Service Office are the samples of this study. The sample collection method used a questionnaire and was analyzed using Partial Least Square with WarpPLS 7.0 software. The results of this study indicate that individual taxpayer compliance is influenced by knowledge of taxation and tax sanctions, the effect of tax knowledge on individual taxpayer compliance cannot be mediated by taxpayer awareness and the effect of tax sanctions on individual taxpayer compliance can be partially mediated by awareness taxpayer.